Effect of the Surface Chemistry of Insulin Fibrils on the Aggregation Rate. Issue 1 (2nd December 2013) - Hsieh, Shuchen; Hsieh, Chiung‐Wen; Chou, Hsuan‐Hung; Chang, Chiung‐Wen; Chu, Ling‐Ya
<x xml:space="preserve">Abstract</x> Structure transition cascade: Insulin fibrils undergo a secondary structural transition—from the α‐rich to the β‐rich form—upon progressively increasing the incubation time from 0.5 to ten hours. Atomic force microscopy measurements show that the fibril surface chemistry changes from hydrophilic to hydrophobic and the aggregation rate increases fivefold.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>